1977
DOI: 10.1172/jci108841
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations of Platelet Aggregation and Secretion

Abstract: A B S T R A C T The mechanism of stimulus-response coupling in human platelets was investigated with a new instrument that simultaneously monitors aggregation and secretion in the same sample of plateletrich plasma. When platelets were stimulated by high concentrations of ADP, secretion began only after aggregation was almost complete. With lower concentrations of ADP or with epinephrine, biphasic aggregation was observed, and secretion began simultaneously with, or slightly after, the second phase of aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
117
2

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(128 citation statements)
references
References 13 publications
9
117
2
Order By: Relevance
“…Our present hypothesis is that platelets exposed to AA in the presence ofdazoxiben, which do not form TxA2, are desensitized at the endoperoxide receptor level, thus failing to aggregate when re-exposed to AA, but are not desensitized to TxA2 and thus retain the ability to respond to it during the second phase (Figure 6f). In this scheme, we suggest that the endoperoxides are responsible for platelet aggregation and secretion, whereas TxA2 causes the initial cell-to-cell approximation before secretion-dependent irreversible aggregation is triggered, as reported for the early stages of primary aggregation by ADP (Charo et al, 1977).…”
Section: Discussionsupporting
confidence: 58%
“…Our present hypothesis is that platelets exposed to AA in the presence ofdazoxiben, which do not form TxA2, are desensitized at the endoperoxide receptor level, thus failing to aggregate when re-exposed to AA, but are not desensitized to TxA2 and thus retain the ability to respond to it during the second phase (Figure 6f). In this scheme, we suggest that the endoperoxides are responsible for platelet aggregation and secretion, whereas TxA2 causes the initial cell-to-cell approximation before secretion-dependent irreversible aggregation is triggered, as reported for the early stages of primary aggregation by ADP (Charo et al, 1977).…”
Section: Discussionsupporting
confidence: 58%
“…32) Collagen-activated platelets require an adequate concentration of intracellular Ca 2ϩ for aggregation, because the formation of platelet is accompanied by the migration of platelets and their adhesion. However, GC significantly blocked Ca 2ϩ release which seems to be critical to the GC-mediated inhibition of platelet aggregation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a polyclonal antibody directed against a 23-kDa heparin-binding fragment of bovine thrombospondin was also observed to inhibit platelet secretion [16]. Previous studies have shown that at low thrombin concentrations secretion lagged behind the first phase of aggregation [64]. By inhibiting platelet aggregation P8 may also indirectly affect secretion.…”
Section: Discussionmentioning
confidence: 99%